Pulmonary Hypertension in Pregnancy: A Case Report - Wasyanto, Trisulo; Anggraini, Nutria Widya Purna (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Pulmonary Hypertension (PH) is a disease characterized by distressing symptoms and decreased life expectancy due to the narrowing of the blood vessels of the lungs, which often leads to right heart failure. The prevalence of PH in women is 97 cases per million, with 64% of the main causes of PH in pregnancy congenital heart defects, resulting in a very high maternal and fetal mortality rate. Case Report: A 38-year-old G4P1A2 31-week gestational age complained of shortness of breath for 5 days. Physical examination revealed blood pressure was 107/62 mmHg, Heart Rate was 98 beats per minute, respiration 40x per minute, and SpO2 88% with NRM 10 Lpm. The heart examination obtained heart sound I -II regular and a systolic murmur was heard between the left 2nd ribs. Abdominal examination was single fetus, intrauterine, breech presentation, His (+), fetal heart rate 160 beats per minute. vaginal toucher 2 cm in labour. ultrasound examination singles fetal, transverse lies, with an estimated fetal weight of 1600 grams. Echocardiography finding: ASD II L to R shunt with LV EF 60%(T), 62% (S), dilated RA-RV, TR severe, MR mild, High Probability of Pulmonary Hypertension. The patient was diagnosed with Dyspnea, Pulmonary edema caused by cardiogenic, ASD II, High probability of PH, NYHA IV, and Breech presentation in labor. Decided to perform a caesarian section and sterilization. The Male baby was born with 1570 grams Apgar Score 3-5-7. post operation patient was admitted to ICU. Twelve hours after the operation the patient had decreased control and became a PH crisis then the patient was declared dead. Results: The death of the patient, in this case, was caused by cardiogenic shock due to Pulmonary Hypertension Crisis. Conclusion: Early diagnosis along with collaborative and comprehensive management of pulmonary hypertension is needed for good maternal and fetal outcomes. Keywords: pulmonary hypertension, pregnancy, heart disease. Correspondence: Trisulo Wasyanto. Department of Cardiology and Vascular Medicine, Faculty of Medicine, Sebelas Maret University / Dr. Moewardi Hospital. Jl. Kol. Sutarto 132, Surakarta 57126, Central Java, Indonesia. Email: trisulo.wasyanto@staff.uns.ac.id. Mobile: +62811294225.